Development of Measurement Instrument of Translation Motion in Constant Acceleration Experiment using Infrared Obstacle Avoidance Sensor Module and MPU 6050 Based on ATmega32U4 Microcontroller - Ilham Hafidzh Wijaya; Yohandri Yohandri; Asrizal Asrizal; Yulkifli Yulkifli (Journal of Experimental and Applied Physics, 2023)
Physics is a field of study that holds significant influence in the development of science and technology. Many natural phenomena are related to physics and can be explained through experiments. From the results of conducted research, it is known that measurements for Translation Motion in Constant Acceleration experiments were carried out manually using standard measuring tools. The limitations of these measuring tools rendered the process impractical and susceptible to errors. To overcome these limitations, an experimental device equipped with automated digital measurement instruments was developed. The objective of this research is to ascertain the design specifications and performance specifications of the experimental device. The performance specifications of the experimental device include a track length of 2 meters and a width of 13mm. It involves the use of a servo motor, Infrared Obstacle Avoidance Sensor Module, and MPU 6050. The design specifications of the experimental device include an angle measurement accuracy of 92%, time measurement accuracy of 89%, velocity measurement accuracy of 87%, and time measurement precision of 92%. So, it is concluded that the measurement instrument can work properly.